Visual communication and its importance for the social media promotion of community-based tourism microenterprises of the Ecuadorian coastpromotion of community-based tourism microenterprises of the Ecuadorian coast - Guillén Matamoros, Andrea Carolina; Rengifo Rengel, Daniela Yamile; Tumbaco Franco, Alexandra Juliana (Scripta Mundi, 2023)
The present research focuses on visual communication and its importance for the social media promotion of community-based tourism microenterprises on the Ecuadorian coast. The methodology used employs content analysis to businesses in three coastal provinces: Guayas, Santa Elena, and Manabi for the data interpretation through observation on these platforms. It allows the identification of the visual content of the tourism entrepreneurships in their social media and their relevance for touristic promotion. Among the results, it´s observed that the communes make publications on a regular basis, where videos and photos are found, although in their entirety, they do not reflect an adequate lay out and the graphic pieces lack good editing. Therefore, it´s concluded that community-based tourism microenterprises on the Ecuadorian coast in the provinces previously mentioned require greater attention in the use of social media so that the dissemination of their content is effective.